Monte Carlo Simulation for Tire and Oil Inventory Optimization at PT X - Augusto, Hengky; Anestesia Purba, Arini; Aprillia, Happy (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
PT X is a distributor of genuine and aftermarket spare parts such as batteries, tires, oil, and other components for various types of cars and trucks. Currently, PT X places orders only when the product inventory is very low or depleted without considering the optimal stock quantity. As a result, PT X often experiences stockouts when there is consumer demand, especially for tires and oil products, whose stock levels frequently fall below the company’s standard inventory levels. This study aims to address the issue of product availability for tires and oil by implementing an effective inventory control method. The methods used in this study include FSN analysis to classify inventory priorities based on their movement rate, Monte Carlo simulation to predict product sales in upcoming periods, and the determination of safety stock and reorder point to prevent future stockouts. The data processed in this study are the purchase and sales data of 25 tire and oil products during the period from March to August 2023, during which 25 products experienced stockouts. The results of the study show that by using FSN analysis, Monte Carlo simulation, and the determination of safety stock and reorder point, PT X can prioritize tire and oil products with high inventory turnover rates for special attention, optimize the inventory of tire and oil products by predicting future sales volumes, and reduce the risk of stockouts by determining safety stock levels and reorder points.